Isoxazole-Based Electrolytes for Lithium Metal Protection and Lithium-Sulfurized Polyacrylonitrile (SPAN) Battery Operating at Low Temperature. Issue 3 (1st March 2022) - Tan, Sha; Liu, Haodong; Wu, Zhaohui; Weiland, Conan; Bak, Seong-Min; Ronne, Arthur; Liu, Ping; Whittingham, M. Stanley; Shadike, Zulipiya; Hu, Enyuan; Yang, Xiao-Qing
Abstract : A new electrolyte system using isoxazole as the salt dissolving solvent has been developed and studied for lithium metal batteries. By using fluoroethylene carbonate (FEC) as an additive and 1, 1, 2, 2-tetrafluoroethyl-2, 2, 3, 3-tetrafluoropropyl ether (TTE) as a diluent for localized high concentration electrolyte (LHCE), isoxazole-based electrolytes were successfully implemented in lithium metal batteries, demonstrating excellent lithium metal protection capability. Utilizing several advanced characterization techniques (including synchrotron-based X-ray absorption spectroscopy and photoelectron spectroscopy), the solid electrolyte interphase (SEI) formed on the Li-metal anode after employing these electrolytes was thoroughly investigated. The high ionic conductivity of isoxazole at low temperature and the low impedance of SEI formed in LHCE significantly improved the low-temperature performance of Li-sulfurized polyacrylonitrile (SPAN) batteries, delivering 273.8 mAh g −1 capacity at −30 °C with 99.85% capacity retention after 50 cycles.